Association between glutathione S-transferase M1, P1, and NFKB1 polymorphisms and systemic lupus erythematosus susceptibility: a meta-analysis - Lee, Y H; Song, G G (Cellular and Molecular Biology, 2016)
This study aimed to determine whether Glutathione S-transferase M1 (GSTM1), P1 (GSTT1), NFKB1 polymorphisms confer susceptibility to systemic lupus erythematosus (SLE). We performed a meta-analysis on the associations between GSTM1 and GSTT1 null genotypes, and NFKB1 -94 ins/delATTG polymorphisms and SLE. In total, seven studies were considered for this meta-analysis, which comprised 2,119 SLE patients and 3,014 healthy controls. Meta-analysis of the GSTM1 null polymorphism in 869 SLE and 1,544 control subjects revealed an association between SLE and the GSTM1 null genotype (OR = 1.321, 95% CI = 1.103–1.583, p = 0.002). Stratification by ethnicity indicated an association between the GSTM1 null genotype and SLE in Asians (OR = 1.334, 95% CI = 1.096–1.623, p = 0.004). However, meta-analysis of the GSTT1 null polymorphism, comprising 717 SLE and 1,008 control subjects, revealed no association between SLE and the GSTT1 null genotype overall (OR = 0.850, 95% CI = 0.687–1.051, p = 0.113) or in an Asian population (OR = 0.794, 95% CI = 0.594–1.061, p = 0.119). Meta-analysis of the NFKB1 -94 ins/delATTG polymorphism, comprising 1,250 SLE and 1,127 control subjects, revealed an association between SLE and the NFKB1 D allele (OR = 1.127, 95% CI = 1.011–1.257, p = 0.031). Ethnicity-specific meta-analysis revealed an association between the NFKB1 D allele and SLE in Asians (OR = 1.155, 95% CI = 1.026–1.300, p = 0.017). This meta-analysis demonstrates that the functional GSTM1 and NFKB1 polymorphisms are associated with the SLE risk in Asians.